Indonesia’s SSB tax policy plan: a review - Budi, Novrialdi Budi Putra (Journal of Applied Sciences in Accounting, Finance, and Tax, 2025)
The purpose of this study is to find out whether the extensification of the excise object of Packaged Sweetened Beverages (SSBS) can have the opportunity to reduce the number of people suffering from non-communicable diseases. The research method uses a literature study approach, the data source is secondary data from the collection of SCOPUS-accredited journals, SINTA, books, and related documents. Analysis is used with an exploratory approach. The results of the study revealed that the imposition of excise on SSBS can reduce purchase interest in products with high sugar content due to an increase in product prices, the imposition of excise also has a great opportunity for educational moments and increasing awareness in the community of the importance of a healthy lifestyle.